Effects of sowing periods on sunflower cultivars in the South of the State of Tocantins - Santos, Elonha (2011)
This study had as its objective, evaluating the agronomic performance of sunflower (Helianthus annuus L.) cultivars when sown at different times, under the environmental conditions in the south of the State of Tocantins. The experiment was carried out during the 2008/2009 agricultural year, in randomized blocks in a 4 x 5 factorial design (four sowing dates and five sunflower cultivars) with three replications. Each plot consisted of four rows 5.0m in length, spaced 0.80 m apart with 0.20 m between plants. For all sowing dates, the characteristics evaluated were: flowering, plant height, stem diameter, head diameter, normal achenes, grain weight per thousand and grain yield. There was significant correlation of sowing dates with the evaluated cultivars for the traits of flowering, plant height and grain yield. In relation to periods of sowing, there was generally a negative influence on all evaluated traits for the later dates, due to an Indian summer causing moisture stress during the critical period of plant development and the occurrence of disease, especially alternaria leaf-spot. The first sowing period (November) showed higher productivity with an average of more than 3,000 kg ha-1. Irrespective of sowing dates, the more productive cultivars were the hybrids Helio 360 and Helio 884, with an average of 1,709 and 1,697 kg ha-1 respectively.